Energetic-environmental assessment of a scenario for Brazilian cellulosic ethanol - Agostinho, Feni [UNESP]; Ortega, Enrique (Elsevier B.V., 2013)
The end of the age of cheap oil and global warming are causing worldwide concerns about energy security and climate change mitigation. Recognizing that the continuous growth paradigm will not change at short to medium time periods, alternative energy sources to fossil fuels are being sought, in which a promising source seems to be that obtained from vegetal biomass. Specifically in Brazil, there are Conventional Ethanol Plants (CEP) using sugarcane, but due to the energy versus food debate and an increasing demand for ethanol, cellulosic ethanol produced by Biorefineries seems to be a viable option. The question is whether the Biorefinery is more sustainable than CEP. This work aims to assess the energetic-environmental performance of a Biorefinery scenario in Brazil, comparing its results against CEP and another alternative small-scale system. For this, a multi-criteria approach was considered through the following methodologies: Embodied Energy Analysis, Ecological Rucksack, Emergy Accounting and Gas Emission Inventory. Results show that Biorefinery scenario has better rating than CEP for the most indicators when the functional unit is mass of ethanol produced, but when dealing with overall system performance, the Biorefinery performance worse. Neither the Biorefinery nor CEP was superior for all indicators, showing the existence of a trade-off. On the other hand, the small-scale system suggests being the best alternative if the aim is to get higher energetic-environmental performance. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Biorefinery; Brazil; Emergy; Energy; Ecological rucksack; Gas emission